Characteristics of Neck Pain in Medical Students of Muhammadiyah Jakarta University Class of 2019 After Online Class for One Semester - Kasmi, Raras Sakti Mulya; Hamzah, Zaini (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Neck pain is a very common complaint in everyday life. Neck pain is a multifactorial disease with many associated risk factors. In population studies, 20-60% of women and 15-40% of men have experienced neck pain. Neck pain is a health problem that can develop and interfere with a person daily activity. Method: This research is a descriptive analytic survey research, which aims to know about neck pain of the students of the Medical Education Study Program Class of 2019. approach used in this study is "cross sectional study", with a total sample of 113 respondents. Result and Discussion: From the 113 respondents the results of research conducted through a questionnaire, there were 76 respondents (67,3%) who experienced neck pain. In the category based on the length of sitting, 76 respondents (67,3%) experienced complaints of neck pain and the results of statistical analysis (P = 0.455) where there was a significant relationship between the length of sitting and complaints of neck pain. In the category of the relationship between the most frequent learning position, there were 76 respondents (67,3%) and the results of statistical analysis (P = 0.586), there was no significant relationship in the most frequent learning position with neck pain complaints and in the learning location category 76 respondents (67,3%) and the results of statistical analysis (P = 0.315), namely that there was no significant relationship in the category of study location with neck pain complaints. Conclusion: There is no significant relationship between learning position and length of sitting with complaints of neck pain in students of 2019 Medicine Program of Muhammadiyah Jakarta University. Because, the sitting position and length of sitting are not the only factors that cause neck pain complaints Â